Critical Exploration and Updated Review on COVID-19 (Asian Journal of Pharmaceutics (AJP), 2023)
Coronaviruses (COVID-19) belong to a group of viruses that can harm the respiratory and digestive systems.Everyone is susceptible to respiratory infections, which depend on the illness and can last from a mild cold tomore serious illnesses. There are two Middle Eastern Respiratory Syndrome Coronavirus (MERS-CoV) cases:Chronic obstructive pulmonary disease and MERS. An updated version of coronavirus, that is, novel coronavirusrecently originated in human beings. Coronavirus is the unit thus named as a result of the means that they seemunderneath a magnifier. The virus comprises a genetic material core of genetic material encased within a spikelikeassociate degree envelope. In Latin, the term corona refers to “corona.” Coronaviruses can spread fromanimals to people since they are an ailment that affects animals. MERS-CoV and SARS-CoV can transfer fromcats and camels to humans, respectively. On December 31, 2019, a bunch of cases of respiratory illness ofunidentified cause, within the town of the city, Hubei region in China, informed by the World Health Organization(WHO). All revealed inherited sequences of SARS-CoV-2 remote from human cases square measure analogous.In 2020, an antecedently unidentified latest virus was known, afterward called the 2019 novel coronavirus, and thesection obtained from cases and studies of the virus’ biological science direct the reason for happening. The WHOrecognized the existence of this novel coronavirus in the year 2020. It was named COVID-19 or CoronavirusInfectious Disease-2019. The illness caused by the virus, SARS-CoV-2, is known as COVID-19.